PHOTO ELASTIC METHOD TO OBSERVE RESIDUAL STRESSES IN COMPACT DISC - Llosa D., Melchor (2005)
The residual stresses and the molecular direction through a product provide the important information on how that product will behave. This is an important preoccupation in the production of plastics by the uses such as information storage. In this work a method of optional non-destructiva testing of evaluation of the quality of compact discs was evaluated and a quantitative analysis became of the state of different tension of CD's.